A comparison of commercial light-emitting diode baited suction traps for surveillance of Culicoides in northern Europe - Andrew Hope; Simon Gubbins; Christopher Sanders; Eric Denison; James Barber; Francesca Stubbins; Matthew Baylis; Simon Carpenter (Parasites & Vectors, 2015)
Abstract Background The response of Culicoides biting midges (Diptera: Ceratopogonidae) to artificial light sources has led to the use of light-suction traps in surveillance programmes. Recent integration of light emitting diodes (LED) in traps improves flexibility in trapping through reduced power requirements and also allows the wavelength of light used for trapping to be customized. This study investigates the responses of Culicoides to LED light-suction traps emitting different wavelengths of light to make recommendations for use in surveillance. Methods The abundance and diversity of Culicoides collected using commercially available traps fitted with Light Emitting Diode (LED) platforms emitting ultraviolet (UV) (390 nm wavelength), blue (430 nm), green (570 nm), yellow (590 nm), red (660 nm) or white light (425 nm – 750 nm with peaks at 450 nm and 580 nm) were compared. A Centre for Disease Control (CDC) UV light-suction trap was also included within the experimental design which was fitted with a 4 watt UV tube (320-420 nm). Generalised linear models with negative binomial error structure and log-link function were used to compare trap abundance according to LED colour, meteorological conditions and seasonality. Results The experiment was conducted over 49 nights with 42,766 Culicoides caught in 329 collections. Culicoides obsoletus Meigen and Culicoides scoticus Downes and Kettle responded indiscriminately to all wavelengths of LED used with the exception of red which was significantly less attractive. In contrast, Culicoides dewulfi Goetghebuer and Culicoides pulicaris Linnaeus were found in significantly greater numbers in the green LED trap than in the UV LED trap. The LED traps collected significantly fewer Culicoides than the standard CDC UV light-suction trap. Conclusions Catches of Culicoides were reduced in LED traps when compared to the standard CDC UV trap, however, their reduced power requirement and small size fulfils a requirement for trapping in logistically challenging areas or where many traps are deployed at a single site. Future work should combine light wavelengths to improve trapping sensitivity and potentially enable direct comparisons with collections from hosts, although this may ultimately require different forms of baits to be developed.